Dampak Keterlambatan Pemberitahuan Pengambilalihan Saham Perusahaan Terhadap Larangan Praktik Monopoli Dan Persaingan Usaha Tidak Sehat - Nasrulloh, Moch Dzulyadain (Universitas Negeri Surabaya, 2021)
A company acquisition is a legal act performed by a legal entity or an individual to take over the company's shares by buying shares or part or all of the company's assets. Acquisition provisions are regulated in Law Number 40 of 2007 concerning Companies and Government Regulation Number 27 of 1998. One of the legal problems in the acquisition of a company is the delay in reporting the acquisition of shares in need. This study aims to analyze the share acquisition mechanism according to Law Number 40 of 2007, Law Number 5 of 1999 and Government Regulation Number 57 of 2010 as well as the legal provisions on the delay in reporting of share takeover faced by PT. Plaza Indonesia Realty, Tbk, which acquired PT. Citra Asri Property. The method used in this research is normative juridical. Data collection techniques in research using literature study with data sources of primary legal materials and secondary legal materials. The result of this research is that in the takeover of PT. Citra Asri Properti has caused several legal consequences, namely: legal consequences for shareholders, legal consequences for employees and legal consequences for the company's organs. This legal effect only affects the shares that are transferred from the old owner to the new owner and the rest remains valid as before. Due to the late reporting violation of the share takeover of PT. Indo Plaza Indonesia Reality, Tbk as stipulated in the applicable fines in Article 6 of Government Regulation Number 57 of 2010